The Effectiveness of Role-Playing Group Counseling Techniques in Improving Students’ Polite Attitudes toward Teachers: Efektivitas Teknik Konseling Kelompok Role Playing dalam Meningkatkan Sikap Sopan Santun Siswa terhadap Guru - Widodo, Bernardus; Berliandika, Ruly (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
Polite behavior is a fundamental aspect of social interaction, particularly within the school environment as a medium for shaping students’ character. However, at SMP Negeri 14 Kota Madiun, several students are still found to have limited understanding and inconsistent application of polite behavior toward teachers. This study aims to analyze the effectiveness of group counseling services using the role-playing technique in improving students’ polite behavior. The research population consisted of 31 students from class VII C at SMP Negeri 14 Kota Madiun, with a sample of 7 students selected based on their low category in practicing politeness. This research employed an experimental method with a pre-experimental one group pretest-post test design. The research instrument was a politeness behavior questionnaire administered before and after the treatment. The results showed an increase in students’ polite behavior after participating in group counseling with the role-playing technique. The average pretest score of 87.4 increased to 113.5 in the posttest, with a significance test (2-tailed) result of 0.001 ≤ 0.005, indicating a significant difference between pretest and posttest scores. Thus, it can be concluded that group counseling services using the role-playing technique are effective in enhancing students’ polite behavior toward teachers